Estudo da estimativa da incerteza de medição para determinação do BS&W e da vazão aplicado no laboratório de avaliação de medição do petróleo - Quintaes, Filipe de Oliveira (2006)
The considered work presents the procedure for evaluation of the uncertainty related to the calibration of flow measurers and to BS&W. It is about a new method of measurement purposed by the conceptual project of the laboratory LAMP, at Universidade Federal do Rio Grande do Norte, that intends to determine the conventional true value of the BS&W from the total height of the liquid column in the auditor tank, hydrostatic pressure exerted by the liquid column, local gravity, specific mass of the water and the specific mass of the oil, and, to determine the flow, from total height of liquid column and transfer time. The calibration uses a automatized system of monitoration and data acquisition of some necessary largnesses to determine of flow and BS&W, allowing a better trustworthiness of through measurements